Self-applied sphenopalatine ganglion block for postdural puncture headache: four case reports - Rocha-Romero,Andrés (2020)
Abstract Background and objectives The Sphenopalatine Ganglion Block (SGB) is an effective, low-risk treatment option for Postdural Puncture Headache (PDPH) refractory to conservative management. Case report This report presents four complex cases of patients with headache related to low cerebrospinal fluid pressure. Three of them were successfully treated with the application of local anesthetic topical drops through the nasal cavity. Conclusion The novel approach described in this report has minimal risks of discomfort or injury to the nasal mucosa. It is quick to apply and can be administered by the patient himself.